High energy storage density of tetragonal PBLZST antiferroelectric ceramics with enhanced dielectric breakdown strength. Issue 3 (15th February 2020) - Zhang, Yujing; Liu, Pin; Shen, Meng; Li, Wenru; Ma, Weigang; Qin, Yanfeng; Zhang, Haibo; Zhang, Guangzu; Wang, Qing; Jiang, Shenglin
Abstract: Tetragonal PBLZST antiferroelectric ceramics is the most studied energy storage material because of its unique double hysteresis loops. However, the dielectric breakdown strength of PBLZST is relatively low, which severely restricts to acquire high energy storage density. In this paper, the PBLZST: x MgO ceramics are synthesized by a two-step calcining method. High-temperature calcination of PBLZST can reduce its activity and inhibit the diffusion between PBLZST and MgO. By regulating the amount of MgO, the influence on the microstructure and properties of PBLZST are systematically researched. As the amount of MgO increases from 0 to 0.2 wt%, the dielectric breakdown strength enhances from 175.2 to 265.2 kV/cm. The PBLZST: x MgO ceramics reach its highest recoverable energy density (5.02 J/cm 3 ) at x = 0.1 wt%. And, its energy storage density only changes by 15.7% with the temperature ranging from 25 to 120 °C. Results prove that introducing MgO into PBLZST with a two-step calcining method can effectively enhance the dielectric breakdown strength.